Profile of olaparib in the treatment of advanced ovarian cancer - Chase DM; Patel S; Shields K (Dove Medical Press, 2016)
Dana M Chase,1,2 Shreya Patel,2,3 Kristin Shields4 1Division of Gynecologic Oncology, The University of Arizona Cancer Center, 2Division of Gynecologic Oncology, 3Creighton University School of Medicine, St Joseph’s Hospital and Medical Center, Phoenix, AZ, 4Department of Trauma, Critical Care, and Acute Care Surgery, Medical College of Wisconsin, Milwaukee, WI, USA Abstract: Olaparib is a poly(ADP-ribose) polymerase inhibitor that received accelerated approval from the US Food and Drug Administration as monotherapy for patients with germline BRCA mutations and ovarian cancer treated with three or more prior lines of chemotherapy. This article summarizes the mechanism of poly(ADP-ribose) polymerase inhibition, therapeutic profile and uses of olaparib, and current and ongoing literature pertaining to olaparib in advanced ovarian cancer. Keywords: olaparib, PARP, ovarian cancer